A multifunctional photothermal nanoplatform integrating CD47 degradation and metabolic reprogramming for potentiated tumor immunotherapy - Jiaming Zhang; Chao Chen; Zhousheng Lin; Zeyu Liu; Juan Zhang; Jieying Qian; Xiaowan Huang; Yunjiao Zhang; Guangyu Yao (Chemical Engineering Journal, 2026)

Thermally regenerable zwitterionic metal-organic frameworks with proton transfer properties for efficient lithium extraction - Xu Wu; Qian Guan; Mengyu Tang; Yue Zheng; Zhipeng Luo; Qiuyue Liu; Jiaming Gan; Xin Yu; Ranwen Ou (Chemical Engineering Journal, 2026)

Machine vision-based impurity content assessment of paddy grains for pre-storage quality monitoring - Liu Yang; Xinfeng Hu; Can Shu; Jiaming Wang; Nianwu Wei; Tianqing Liu; Qian Liu; Menghao Zhao; Zhiwei Liu; Shaoyun Song (Journal of Stored Products Research, 2026)

Nickel from olivine dissolution induces diel photodamage and metabolic adjustment in Gracilariopsis lemaneiformis - Chang Liu; Dong Xu; Xuewei Wang; Yiqun Wu; Yuan Chang; Jiaming Zhang; Xinyu Qian; Ling Liu; Ping Li; Zhi-Hua Li (Journal of Hazardous Materials, 2026)

Abscisic acid promotes watercore dissipation by accelerating sorbitol decomposition through the MdNAC25-MdSDH8 module in apple fruit - Yali Li; Hao Wei; Qian Ma; Jiaming Li; Zuanhong Xu; Yamei Ren; Xiaolin Ren; Yuduan Ding (Postharvest Biology and Technology, 2026)

Revealing the antioxidant potential of Artemisia integrifolia L.: Integrated discovery of bioactive compounds via UHPLC-DPPH and activation of the Nrf2/HO-1 signaling pathway - Huimin Li; Qian Gao; Yijin Wu; Jingya Ruan; Jiaming Cheng; Yi Zhang; Tao Wang (Phytochemistry, 2026)

Olfactory Valence-Processing Deficits and Aberrant Brain Network Connectivity Underlie Social Dysfunction in Shank3-/- ASD Model Mice - Dingding Yang; Qian Liu; Hangjun Ran; Teng Xue; Yifan Lu; Xiao Yang; Jiaming Wang; Ling Liu; Wenting Wang; Binbin Nie; Guohong Cai; Shengxi Wu (Neuroscience Bulletin, 2026)

Determining the age of Guadalupian extinction by in situ uranium–lead geochronology in regard to middle Permian giant bivalve Alatoconchidae fossils in the Northwest margin of the South China Plate - Xueqin Zhao; Ran Liu; Fudong Wang; Qian Li; Chen Su; Jiaming Ding; Caifu Xiong; Wentao Li; Jianhua Zhang; Keli Hou (Gondwana Research, 2026)

Unlocking ultrahigh anion adsorption in sunlight-responsive metal-organic frameworks for water purification - Xu Wu; Qian Guan; Mengyu Tang; Yilei Fang; Jiaming Gan; Xinyu Zhang; Xin Yu; Ranwen Ou (Chemical Engineering Journal, 2026)

A bead-based dendritic amplification system for multiplex miRNA detection - Feiyang Qian; Rui Zhu; Yao Lu; Tenghua Zhang; Yuqing Zhu; Yan Sheng; Jiaming Hu (Chemical Engineering Journal, 2026)

Flexible CeO₂ surface engineering optimizes atomically dispersed Ru catalyst-support interaction for enhanced ammonia decomposition - Xuehan Hu; Bin Guan; Lei Zhu; Chenyu Zhu; Zhongqi Zhuang; Sikai Zhao; Junyan Chen; Kaiyou Shu; Hongtao Dang; Junjie Gao; Luyang Zhang; Tiankui Zhu; et al. (Chemical Engineering Journal, 2025)

Pd/F-Al2O3 catalyst for N2O-NH3-SCR with ultrahigh low-temperature activity and resistance to inhibitory gases: Property research of being rich in oxygen vacancies with free electrons and reaction mechanisms - Zhongqi Zhuang; Bin Guan; Lei Zhu; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Kaiyou Shu; Hongtao Dang; Junjie Gao; Luyang Zhang; Tiankui Zhu; et al. (Chemical Engineering Journal, 2025)

Study on the division method of the excavation disturbed zone in tunnels based on continuous-discontinuous theory - Jixu Zhang; Xiaodong Fu; Chao Tan; Yongqiang Zhou; Qian Sheng; Chen Xu; Jiaming Wu (Bulletin of Engineering Geology and the Environment, 2025)

Associations of wildfire-derived particulate matter with hospitalization, emergency department visits and mortality: A systematic review and meta-analysis - Yiyi Wang; Jie Chen; Yujia Huang; Jiaming Wang; Yi Xiong; Tao Xue; Xu Yue; Fuping Qian; Meng Wang (Environmental Research, 2025)

Unmet needs of patients with intravascular large B-cell lymphoma: three case reports and a literature review - Xian Li; Ru Luo; Jiaming Xu; Xueli Jin; Weiqin Wang; Xibin Xiao; Wenbin Qian (Journal of Zhejiang University-SCIENCE B, 2025)

The impact of Neoporphyra haitanensis dietary supplement on astaxanthin esters and fatty acids accumulation associated with immune promotion in Pacific white shrimp (Litopenaeus vannamei) - Qian Shen; Shuang Li; Shuyu Zhang; Jiaming Xu; Haimin Chen; Qijun Luo; Rui Yang; Juanjuan Chen (Aquaculture, 2024)

Prevalence of common upper gastrointestinal diseases in Chinese adults aged 18–64 years - Hong Yang; Mei Zhang; Hui Li; Zhengjing Huang; Yuanyuan Sun; Wenbo Li; Chun Li; Xuzhen Qin; Yanhong Wang; Xiao Zhang; Zhenping Zhao; Limin Wang; et al. (Science Bulletin, 2024)

Alterations in Dynamic Functional Connectivity in Patients with Cerebral Small Vessel Disease - Futao Chen; Qian Chen; Yajing Zhu; Cong Long; Jiaming Lu; Yaoxian Jiang; Xin Zhang; Bing Zhang (Translational Stroke Research, 2024)
Cerebral small vessel disease (CSVD) is a common disease that seriously endangers people’s health, and is easily overlooked by both patients and clinicians due to its near-silent onset. Dynamic functional connectivity (DFC) is a new concept focusing on the dynamic features and patterns of brain networks that represents a powerful tool for gaining novel insight into neurological diseases. To assess alterations in DFC in CSVD patients, and the correlation of DFC with cognitive function. We enrolled 35 CSVD patients and 31 normal control subjects (NC). Resting-state functional MRI (rs-fMRI) with a sliding-window approach and k -means clustering based on independent component analysis (ICA) was used to evaluate DFC. The temporal properties of fractional windows and the mean dwell time in each state, as well as the number of transitions between each pair of DFC states, were calculated. Additionally, we assessed the functional connectivity (FC) strength of the dynamic states and the associations of altered neuroimaging measures with cognitive performance. A dynamic analysis of all included subjects suggested four distinct functional connectivity states. Compared with the NC group, the CSVD group had more fractional windows and longer mean dwell times in state 4 characterized by sparse FC both inter-network and intra-networks. Additionally, the CSVD group had a reduced number of windows and shorter mean dwell times compared to the NC group in state 3 characterized by highly positive FC between the somatomotor and visual networks, and negative FC in the basal ganglia and somatomotor and visual networks. The number of transitions between state 2 and state 3 and between state 3 and state 4 was significantly reduced in the CSVD group compared to the NC group. Moreover, there was a significant difference in the FC strength between the two groups, and the altered temporal properties of DFC were significantly related to cognitive performance. Our study indicated that CSVD is characterized by altered temporal properties in DFC that may be sensitive neuroimaging biomarkers for early disease identification. Further study of DFC alterations could help us to better understand the progressive dysfunction of networks in CSVD patients.

Cas-Rainbow: Cas12a-driven single-reaction multiplex detection system - Yuqing Zhu; Jianming Zhou; Yuxin Liang; Yao Lu; Shujun Zhou; Feiyang Qian; Tenghua Zhang; Yan Sheng; Jiaming Hu (Chemical Engineering Journal, 2024)

A dual amplification-based CRISPR/Cas12a biosensor for sensitive detection of miRNA in prostate cancer - Yuqing Zhu; Xiaohe Zheng; Shujun Zhou; Wenjing Xiao; Xiaorui Sun; Jianming Zhou; Feiyang Qian; Tenghua Zhang; Yan Sheng; Jiaming Hu (Analytica Chimica Acta, 2023)

Tectonomagmatic setting and magmatic Cu-PGE metallogeny during the late Neoproterozoic in the Eastern Kunlun Orogen, NW China: Insights from the Hatu Cu-Pt-Pd-bearing mafic-ultramafic intrusion - Liang Li; Fengyue Sun; Li Wang; Yajing Zhang; Chao Wang; Ye Qian; Tuofei Zhao; Jiaming Yan; Shucheng Tan (Precambrian Research, 2023)

Abundance, characteristics, and removal of microplastics in different wastewater treatment plants in a Yangtze River Delta city of China - Juan Huang; Luming Wang; Jiaming Liu; Xiuwen Qian; Yufeng Wu (Journal of Water Process Engineering, 2023)

CRISPR-Cas12a powered multifunctional DNA nanodumbbell lock biosensor for multiple molecular detection - Yuqing Zhu; Xiaohe Zheng; Rui Zhu; Hongrui Zhao; Hongli Zhai; Feiyang Qian; Tenghua Zhang; Zihui Xie; Silan Liu; Bowen Jiang; Yan Sheng; Jiaming Hu (Chemical Engineering Journal, 2023)

Brain microstructural alterations in the left precuneus mediate the association between KIBRA polymorphism and working memory in healthy adults: a diffusion kurtosis imaging study - Junxia Wang; Sichu Wu; Yi Sun; Jiaming Lu; Jilei Zhang; Yu Fang; Zhao Qing; Xue Liang; Wen Zhang; Qian Chen; Xin Zhang; Bing Zhang (Brain Imaging and Behavior, 2022)
Kidney and brain expressed protein (KIBRA) rs17070145 is associated with working memory function and cognitive processes. However, the neural mechanisms underlying these associations are not fully understood. This study aimed to explore the effect of KIBRA polymorphism on brain microstructure and blood oxygenation level dependent (BOLD) fluctuations using diffusion kurtosis imaging (DKI) and resting-state functional magnetic resonance imaging (fMRI) in 163 young adults. We also investigated that whether the imaging alterations mediated the association between KIBRA gene and working memory performance. Voxel-based analysis of DKI data showed that KIBRA C-allele carriers exhibited increased axial diffusivity (AD), radial diffusivity (RD) and mean diffusivity (MD) as well as decreased fractional anisotropy (FA), mean kurtosis (MK) and radial kurtosis (RK) compared with KIBRA TT homozygotes, primarily involving the prefrontal lobe, left precuneus and the left superior parietal white matter. Meanwhile, KIBRA C-allele carriers exhibited decreased amplitude of low-frequency fluctuation (ALFF) in the left precuneus compared to KIBRA TT homozygotes. Mediation analysis revealed that the DKI metrics (MK and RK) of the left precuneus mediated the effect of the KIBRA polymorphism on working memory performance. Moreover, the MK and RK in the left precuneus were positively correlated with ALFF in the same brain region. These findings suggest that abnormal DKI parameters may provide a gene-brain-behavior pathway in which KIBRA rs17070145 affects working memory by modulating brain microstructure in the left precuneus. This illustrates that DKI may provide additional biological information and reveal new insights into the neural mechanisms of the KIBRA polymorphism.

Design, synthesis and biological evaluation of indoline derivatives as multifunctional agents for the treatment of ischemic stroke - Shuaishuai Du; Fan Jin; Jiaming Li; Xiaodong Ma; Hongwei Wang; Shihu Qian (Medicinal Chemistry Research, 2022)

Altered resting-state networks may explain the executive impairment in young health immigrants into high-altitude area - Xiaoming Chen; Jian Liu; Jiye Wang; Zhenlong Xin; Qian Zhang; Wenbin Zhang; Yibin Xi; Yuanqiang Zhu; Chen Li; Jiaming Li; Yuedong Han; Jie Liu; et al. (Brain Imaging and Behavior, 2021)

Biological and chemical compositions of atmospheric particulate matter during hazardous haze days in Beijing - Zhendong Guo; Zhongyi Wang; Lu’an Qian; Zongzheng Zhao; Chunmao Zhang; Yingying Fu; Jiaming Li; Cheng Zhang; Bing Lu; Jun Qian (Environmental Science and Pollution Research, 2018)

Effects of crude extracted proteins from supernatant of BCF-P and EGF on acid secretion - Yuqing Zhao; Tao Guo; Jiaming Qian (Molecular & Cellular Toxicology, 2015)

Clinical Analysis of 15 Cases of Liver Nodular Regenerative Hyperplasia - Tao Guo; Jiaming Qian; Liming Zhu; Weixun Zhou; Feng Zhu; Gang Sun; Xiucai Fang (Cell Biochemistry and Biophysics, 2012)

Characterization of transcriptional activation and inserted-into-gene preference of various transposable elements in the Brassica species - Caihua Gao; Meili Xiao; Lingyan Jiang; Jiana Li; Jiaming Yin; Xiaodong Ren; Wei Qian; Ortegón Oscar; Donghui Fu; Zhanglin Tang (Molecular Biology Reports, 2012)

AtRabD2b, a Functional Ortholog of the Yeast Ypt1, Controls Various Growth and Developmental Processes in Arabidopsis - Fang Wang; Chao Liu; Chen Wei; Yuhai Cui; Qian Zheng; Jiaming Zhang; Jiangsheng Wu; Kede Liu (Plant Molecular Biology Reporter, 2012)

Contribution of the IBD5 locus to inflammatory bowel disease: a meta-analysis - Jian Wang; Xi Wang; Hong Yang; Dong Wu; Li Wang; Jiaming Qian (Human Genetics, 2011)